1999
DOI: 10.1200/jco.1999.17.3.1040
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, Knowledge, and Risk Perceptions of Women With Breast and/or Ovarian Cancer Considering Testing for BRCA1 and BRCA2

Abstract: A high proportion of the high-risk women in this study had knowledge deficits about BRCA1 and BRCA2 and overestimated their risk of having a mutation. Although some degree of caution should be used in generalizing the results of this study to practice settings, the data provide insight into the challenges clinicians will face in communicating with patients about cancer genetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(43 citation statements)
references
References 28 publications
2
39
0
2
Order By: Relevance
“…Having prior knowledge that our local population is not generally well informed about medical matters, we felt it important to design a questionnaire assessing only common and important knowledge of breast cancer risk factors and hereditary breast cancer using simplistic language. We have done so by collating and modifying questions used in various previous studies [25, 26, 41, 42]and hope to validate this questionnaire in future studies. Finally, our survey assessed theoretical knowledge and not actual practices.…”
Section: Discussionmentioning
confidence: 99%
“…Having prior knowledge that our local population is not generally well informed about medical matters, we felt it important to design a questionnaire assessing only common and important knowledge of breast cancer risk factors and hereditary breast cancer using simplistic language. We have done so by collating and modifying questions used in various previous studies [25, 26, 41, 42]and hope to validate this questionnaire in future studies. Finally, our survey assessed theoretical knowledge and not actual practices.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in genetic testing has increased commensurately (Jacobs, Latza et al 2001; Dahodwala, Connolly et al 2007; Falcone, Wood et al 2011); however, a range of studies have demonstrated a lack of general (Henneman, Timmermans et al 2004; Catz, Green et al 2005) or disease-specific genetic knowledge among various patient populations including PD patients (Falcone, Wood et al 2011), breast cancer patients (Bluman, Rimer et al 1999; Bluman, Rimer et al 2003), and Huntington disease patients (Semaka, Balneaves et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Overestimation of personal cancer risk is frequently reported by individuals with cancer [59]. Additionally, cancer worries are a critical concern for survivors and their family members and have been linked to increased anxiety, emotional distress, and impaired role functioning [1012].…”
Section: Introductionmentioning
confidence: 99%
“…Perception of cancer risk has consistently been cited as a major factor influencing the decision to undergo genetic counseling and testing by women at increased risk of inherited breast or ovarian cancer [59]. Overestimation of an individual’s risk status has been associated with several negative outcomes, including increased anxiety and distress for one’s self and family members [9, 13], lower perception of control over cancer [9], depression [9], and excessive hyper-vigilance in screening practices [6].…”
Section: Introductionmentioning
confidence: 99%